Belize Blues - Little, Kenneth (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2012)
This is the story of how blue becomes an emergent, world making force of life in Walliceville, Belize. It is a story of attachments to scenes and objects of desire that sustain life in that village, about how blue takes material and imaginative form in the way it pulls some consistency of forces, sensibilities, and materialities into alignment to become the generative textures and rhythms of life in a place going crazy for tourists. My story tracks an eventfulness that erupts out of connections expressing qualities of blue that actualize worlds through a relay of encounters and are sensed through a sustained engagement with the seductive and recalcitrant materiality of that color. It also asks how ethnographic writing may be construed as an act of attuning that wavers from its trajectories to follow stories of blue encounters while attending to things that add to even if they never add up.